Value Estimation Of California Bearing Ratio From Hand Cone Penetrometer Test For Pekanbaru Soils - Nugroho, Soewignjo Agus (Jurnal Teknik Sipil, 2019)
In practice, the design of pavement is commonly based on the California Bearing Ratio (CBR) test. This research was performed to study the local correlation between Hand Cone Penetrometer (HCP) tests to the field CBR value. The local correlation is determined based on comparisons of HCP and CBR test results for the soil with same density which have been taken from several locations in Pekanbaru City, Indonesia. It was found that there is an approximate linear relation in log scale between HCP test results to CBR values for a certain density of soil. Correlation for HCP and density to CBR has been put forward for the local correlation between those two values. Verification of the formula has shown that the correlation can be used relatively accurate for predicting the field CBR values from the HCP test for in-organic soils. For organic soil, the formula needs to be further researched.